2001
DOI: 10.1055/s-0037-1615676
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Tumor Necrosis Factor α Levels and the –238* A Promoter Polymorphism in Patients with Antiphospholipid Syndrome

Abstract: Summary Objectives. To explore the possible involvement of the proinflammatory and prothrombotic cytokine TNFα in APS by determining the plasma levels in patients and to test for association of TNFA promoter polymorphisms and HLA class II genotypes with both plasma TNF and disease. Patients and Method. We studied 83 Caucasoid patients with APS and two groups of healthy controls. TNFα levels were determined in plasma from 35 patients’ and 21 controls using a highly sensitive sandwich ELISA. The full p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 24 publications
5
23
0
1
Order By: Relevance
“…Our results corroborate with those of Bertolaccini et al [25], who showed elevated TNF-a levels in patients with APS. Also, in accordance with our findings, they were unable to show any differences between its primary and secondary form (Table 1).…”
Section: Discussionsupporting
confidence: 93%
“…Our results corroborate with those of Bertolaccini et al [25], who showed elevated TNF-a levels in patients with APS. Also, in accordance with our findings, they were unable to show any differences between its primary and secondary form (Table 1).…”
Section: Discussionsupporting
confidence: 93%
“…Our results were reminiscent of a previous study, in which the TNF-a K238G/A, but not the K308G/A, SNP were associated with RM (Bertolaccini et al 2001). This lack of association of the TNF-a K308G/A SNP with increased RM risk was also reported for Caucasian A recent meta-analysis (Daher et al 2003) confirmed the lack of association of the TNF-a K308G/A SNP with RM, and suggested instead that interferon-g (874T/T) and IL-10 (K1082G/G) gene variants represented stronger RM inherited risk factors.…”
Section: Tnf-a/lt-a Polymorphisms In Idiopathic Rmsupporting
confidence: 87%
“…The present results were reminiscent of an earlier study, in which the TNFa À238G/A, but not the À308G/A, SNP was associated with RM (28). This lack of association of the TNFa À308G/A SNP with increased RM risk was also reported for Caucasian (17,23,28,29) and Iranian (30) women, and in apparent partial disagreement with the study of Costeas et al (21).…”
Section: Discussionsupporting
confidence: 71%